'The worse my hearing got, the less sociable I got': a qualitative study of patient and professional views of the management of social isolation and hearing loss. (18th February 2022) - Heffernan, Eithne; Withanachchi, Christine M; Ferguson, Melanie A
Abstract: Background: Social isolation is a major consequence of hearing loss. It includes an objective component (e.g. small social network) and a subjective component (e.g. loneliness). Objective: To examine the perspectives of key stakeholders regarding (i) the relationship between hearing loss and social isolation and (ii) interventions to address hearing loss and social isolation. Design: A phenomenological qualitative study. Setting: A UK research centre with a role to engage patients and clinicians. Participants: Hearing healthcare professionals ( n  = 7) and adults with hearing loss ( n  = 6) were recruited via maximum variation sampling. Methods: Individual ( n  = 3) and group ( n  = 3) semi-structured interviews were conducted. Inductive thematic analysis was performed. Results: Five themes were identified. Theme 1 (experience of isolation and hearing loss): hearing loss can cause people to feel disconnected at social events or to cease attending them. Theme 2 (complexity of isolation and hearing loss): the various causes of isolation (e.g. hearing loss, retirement, comorbidities) are difficult to disentangle. Theme 3 (downstream effects of isolation and hearing loss): hearing loss and/or isolation can lead to mental health problems, stigmatisation, fatigue and unemployment. Theme 4 (preferred components of an isolation intervention): an isolation intervention should be patient-led and patient-centred and take place in the community. Theme 5 (challenges to implementing an isolation intervention): barriers to implementing an isolation intervention include a lack of time, training and continuity. Conclusion: This study demonstrated that social isolation arising from hearing loss is a substantial, complex problem and provided novel insights on implementing an intervention to address this issue.